BUSINESS MANAGEMENT STRATEGIES FOR SMES IN THE DIGITALIZATION ERA - Anila Dani Sakinah (Study Program of Sharia Business Management , Faculty of Islamic Economics and Business, 2024)
The digitalization era presents both opportunities and challenges for SMEs. To thrive in this new landscape, SMEs must adopt strategic management approaches that leverage digital technologies to enhance customer engagement, optimize internal processes, and ensure cybersecurity. This study employs a qualitative research method to explore the business management strategies of Small and Medium Enterprises (SMEs) in facing the digitalization era. The adoption of digital technologies is crucial for modern business success and sustainability. For SMEs, it levels the playing field with larger corporations by enhancing efficiency, customer experience, and market reach. Automation tools, like accounting software and inventory management systems, save time and resources. CRM systems personalize services and strengthen customer relationships. E-commerce platforms allow global sales and provide consumer insights. Data analytics supports informed decision- making, optimizing pricing, and inventory management. Digital marketing expands reach and engagement, while robust cybersecurity measures protect sensitive data. Continuous digital skills training and collaboration with technology partners ensure SMEs remain competitive.